Performance of Recycled Concrete Made from Railway Sleeper: Experimental Study - S Suharwanto; Wachid Hasyim; Yudha Prakasa (Universitas Islam Sultan Agung, 2021)
Concrete railway sleeper has been used in Indonesia since about 1990’s. It has more advantage that is less maintenance, stabile, good quality, shapeable, onsite raw material, and higher loading ability [9-10, 20 - 22]. But It is prone to damage such as cracking and breaking during construction, so it is often thrown away as a solid waste that can contaminate the land and reduce soil fertility. Therefore, it should be utilized in order to be more useful that is used as recycle aggregate. The concrete waste that is taken from broken concrete railway sleeper will be crush as an aggregate as raw material in the concrete to substitute part or all of the normal concrete. It is called recycled aggregate and concrete that is made from recycled aggregate is called recycled concrete. Base on the testing of raw material, the recycled aggregate can be met to the specification as ASTM [1], so it can be used for concrete raw material. Recycled concrete compressive strength result lower the normal concrete compressive strength in the same initial strength design. The strength value of recycled concrete is decrease about 1 – 17% for 25 MPa and 10 – 18% for 30 MPa. It is also happened to tensile strength of recycled concrete that decrease about 2 – 13 % for 25 MPa and 7 – 22 % for 30 MPa.